2002
DOI: 10.1590/s0074-02762002000700015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the direct agglutination test and the rK39 dipstick test for the sero-diagnosis of visceral leishmaniasis

Abstract: The direct agglutination test (DAT) based on a freeze-dried antigen and the rK39 dipstick test were evaluated for the sero-diagnosis of visceral leishmaniasis (VL). The sensitivity and specificity of both tests were determined using sera from confirmed VL patients (n = 21), healthy controls (n = 19) and from patients with other confirmed infectious diseases (n = 42). The DAT had a sensitivity and a specificity of 100%. The rK39 had a sensitivity of 85.7% and a specificity of 82%. Both tests were also used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
2
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 12 publications
5
27
2
4
Order By: Relevance
“…In Brazil, validation studies of the IT-LEISH TM have reported a sensitivity varying from 93% to 100% and a specifi city between 94% and 96% 18,20 , considering confi rmed cases only as those with a parasitological diagnosis. In addition, the PPV and NPV of 98% and 89%, respectively, were similar to those found in our study.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, validation studies of the IT-LEISH TM have reported a sensitivity varying from 93% to 100% and a specifi city between 94% and 96% 18,20 , considering confi rmed cases only as those with a parasitological diagnosis. In addition, the PPV and NPV of 98% and 89%, respectively, were similar to those found in our study.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…In addition, the PPV and NPV of 98% and 89%, respectively, were similar to those found in our study. Evaluations of the performance of Kalazar Detect TM have shown sensitivity values between 85.7% and 90% and a specifi city between 82% and 100% 18,19 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests are fast and easy to perform and the results are available in less than 20 min on average (Boelaert et al 2007). Studies on rapid tests for VL have found sensitivity and specificity values that range from 67-100% and 59-100%, respectively (Schallig et al 2002, Carvalho et al 2003. However, there are variations among geographic regions and commercially available tests (WHO 2011).…”
mentioning
confidence: 99%
“…However, there are variations among geographic regions and commercially available tests (WHO 2011). Studies have reported false positives when using the rK39 antigen due to cross-reactivity with other protozoans (Schallig et al 2002, Sundar et al 2002. A meta-analysis that involved 13 research centres that used the rK39 rapid test for the diagnosis of VL yielded average sensitivity and specificity values of 93.9% and 90.6%, respectively (Chappuis et al 2006).…”
mentioning
confidence: 99%